“3S Project”: a community-based social marketing campaign for promoting sustainable consumption behavior among youth - Nottakrit Vantamay, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to evaluate a community-based social marketing (CBSM) campaign for promoting sustainable consumption behavior (SCB) among Thai youth. As a result, the “3S Project” was a CBSM campaign innovation to promote SCB among Thai youth which was created and piloted with a small segment of university students. The project was evaluated using quasi-experimental research in the form of a non-equivalent control group, designed for checking the effectiveness. Multivariate analysis of variance (MANOVA) at .05 statistically significant level was employed in this analysis. After intervention, it found that the “3S Project” innovation was effective. The mean scores of the experimental group were higher than the mean scores of the control group significantly in all five indicators, including the attitude towards behavior, the subjective norm, the perceived behavioral control, the intention to perform SCB, and sustainable consumption behavior (SCB). These results were recognized as new findings in the field of social marketing communication. They extend the existing body of knowledge in this field of study because using CBSM for sustainable behavior change in Thailand is still considered as being in its initial stage. Therefore, the results of this research project will be strongly beneficial for social marketing practitioners, communication campaign planners, and any organizations related to promote SCB among youth on all levels (international level, national level, and even local level) in utilizing this CBSM campaign innovation for promoting SCB among the Thai youth, both effectively and efficiently.